HISTORICISING DOMESTIC TERRORISM AND BOKO HARAM INSURGENCY IN THE NORTH EAST, NIGERIA: ISSUES AND TRENDS - Adesote, Adesola Sa; Akande, Adekunle Sunday; Abimbola, John Ojo (Journal of Terrorism Studies, 2024)
Since the return to civil rule in 1999, Nigeria has been battling with series of violent agitations from various geo-political zones in the country. These violent agitations which have taken terror dimensions have contributed to national security threat. Terrorists’ attacks have resulted in the killings of hundreds of people and wanton destruction of property that worth billions of naira through bombings. The major thrust of this paper is to investigate the challenge of domestic terrorism with major emphasis on the activities of the dreaded militant Islamic sect, popularly known as Boko Haram since 2009. The paper argues that most of the circumstances that led to this criminality are not unconnected with frustration caused by high rate of unemployment, poverty and weak governance. It, therefore suggests that Nigeria needs to re-evaluate her domestic and foreign policy directions and objectives towards combating domestic terrorism. It asserts that Nigeria’s domestic terrorism has external connections aid that the country could also be exporting terrorism to other countries in the nearest future if not checked. The methodology adopted in this paper is historical and thematic, utilizing materials from both primary and secondary sources.